2006
DOI: 10.1080/10245330600954163
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume measurement, EDTA or citrate?

Abstract: Most laboratories use EDTA for anticoagulation of whole blood prior to automated cell counting but due to platelet swelling, mean platelet volume (MPV) values may increase with its use. MPV changes may be less with acid citrate based anticoagulation. As MPV is a marker of platelet function and its precise measurement is important in a number of clinical situations, this study was performed to assess if EDTA and citrate based anticoagulated blood samples can be used interchangeably for MPV measurement. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 17 publications
2
93
1
1
Order By: Relevance
“…One of the main limitations of our study is its retrospective design. It was previously shown that blood collected in EDTA tubes should be analyzed within 1 h after collection to prevent platelet swelling [33]. The medical records of our study population did not comprise any information about the processing time.…”
Section: Discussıonmentioning
confidence: 99%
“…One of the main limitations of our study is its retrospective design. It was previously shown that blood collected in EDTA tubes should be analyzed within 1 h after collection to prevent platelet swelling [33]. The medical records of our study population did not comprise any information about the processing time.…”
Section: Discussıonmentioning
confidence: 99%
“…39 A study in literature revealed that both EDTA and citrate can be used for accurately measurement of MPV. 40 Another issue is that, same as RDW, standardizing blood count tests is difficult and the prolongation of the time between blood sampling and assay may cause swelling of the platelets which may mislead increased MPV measurement.…”
Section: Mean Platelet Volumementioning
confidence: 99%
“…5 Mean platelet volume disturbances reflect changes in either the level of platelet stimulation or the rate of platelet production. 6 Moreover, mean platelet volume has been used as an indicator of platelet function for inflammatory diseases, 7 and because inflammation plays a crucial role in COPD, alterations in platelet activity and consequently in the mean platelet volume are expected. Indeed, there are various studies that show a disturbance of mean platelet volume levels in subjects with stable COPD.…”
Section: Introductionmentioning
confidence: 99%